2014
DOI: 10.1007/s10815-014-0399-5
|View full text |Cite
|
Sign up to set email alerts
|

Improved blastocyst formation with reduced culture volume: comparison of three different culture conditions on 1128 sibling human zygotes

Abstract: Purpose The aim of the present randomized, comparative study was to evaluate the effect of reduced culture volumes on sibling human embryo development. Methods Firstly, sibling injected oocytes obtained from 88 out of 165 consenting couples undergoing infertility treatment were cultured either in large (35 μl) or in small drops (15 μl) of culture medium. Secondly, sibling injected oocytes from 77 couples were cultured either in large (35 μl) or in mini drops (7 μl). Embryo quality on day-2 and day-3 and blasto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 31 publications
1
27
1
Order By: Relevance
“…These data are in contrast with those of Minasi et al [10], which may be related to the difference in culture media (Origio in the present study versus Sage by Minasi et al). The two culture media have a different amino acid constitution and concentration and were supplemented with different protein sources.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…These data are in contrast with those of Minasi et al [10], which may be related to the difference in culture media (Origio in the present study versus Sage by Minasi et al). The two culture media have a different amino acid constitution and concentration and were supplemented with different protein sources.…”
Section: Discussioncontrasting
confidence: 99%
“…The recent report by Minasi et al [10] comparing embryo culture in either 35 or 7 μl droplets reported comparable embryo quality on day 3 (∼80 %), but significantly higher blastulation rates on day 5 when embryos were cultured in 7 μl droplets (50.5 versus 70.0 %, p<0.05). It should be noted that the authors did not present data on cell number on day 3 nor on expansion stage and blastocyst quality on day 5.…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations